2018
DOI: 10.3390/ijgi7090337
|View full text |Cite
|
Sign up to set email alerts
|

Using Eye Tracking to Explore Differences in Map-Based Spatial Ability between Geographers and Non-Geographers

Abstract: In this article, we use eye-tracking methods to analyze the differences in spatial ability between geographers and non-geographers regarding topographic maps, as reflected in the following three aspects: map-based spatial localization, map-based spatial orientation, and map-based spatial visualization. We recruited 32 students from Beijing Normal University (BNU) and divided them into groups of geographers and non-geographers based on their major. In terms of their spatial localization ability, geographers had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 50 publications
1
21
2
1
Order By: Relevance
“…Moreover, contrary to some of the previous studies (e.g., [5,38]) it was found that on average successful participants needed more time to solve some of the analyzed tasks. Notwithstanding, this slow task solving is not a feature of inexperienced behavior or inefficient strategy, as it is attributable to their endeavor to solve the task correctly.…”
Section: What Less Successful and More Successful Map Users Do Differcontrasting
confidence: 99%
See 3 more Smart Citations
“…Moreover, contrary to some of the previous studies (e.g., [5,38]) it was found that on average successful participants needed more time to solve some of the analyzed tasks. Notwithstanding, this slow task solving is not a feature of inexperienced behavior or inefficient strategy, as it is attributable to their endeavor to solve the task correctly.…”
Section: What Less Successful and More Successful Map Users Do Differcontrasting
confidence: 99%
“…In addition, even participants who did not work with the scale bar during tasks related to distance estimation can be identified. This outcome is consistent with the results of previous empirical studies (e.g., [16,38,75,76]). Moreover, it is grounded in the novice-expert paradigm as this difference is an implication of the theory of information reduction [33].…”
Section: What Less Successful and More Successful Map Users Do Differsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on visual and statistical analyses of eye-movement recordings, Ooms et al explored the difference in the map memorization abilities of geographers and non-geographers [40]. Dong et al used gaze series parameters (fixation count, fixation frequency) to analyse the differences between geographers and non-geographers in terms of spatial ability regarding topographic maps [15]. Thus, eye tracking is an effective way to study the differences in spatial ability before and after geography courses.…”
Section: Introductionmentioning
confidence: 99%